PENGARUH WORKING CAPITAL TURNOVER, SALES GROWTH DAN CASH TURNOVER TERHADAP NET PROFIT MARGIN PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR LOGAM DAN SEJENISNYA - Eni Nurwati; Untung Sriwidodo; Dorothea Ririn Indriastuti (Universitas Slamet Riyadi, 2020)
The purpose of this study is to analyze the effect of working capital turnover, sales growth, and cash turnover partially and simultaneously on net profit margin. The research population is the metal sub-sector manufacturing companies and the like listed on the Indonesia Stock Exchange in 2015 - 2018 of 16 companies. The sampling technique used purposive sampling with a sample of 13 companies. Data collection techniques used documentation. Data analysis techniques used multiple linear regression, t test, F test and the coefficient of determination. The results of this study indicate that working capital turnover has a positive and significant effect on net profit margin. Sales growth has a positive and significant effect on net profit margin. Cash turnover has a negative and significant effect on net profit margin. Working capital turnover, sales growth and cash turnover has a effect simultaneously on net profit margin.